Latin American social work practice in the justice system - Reyes-Quilodrán, Claudia (Latin American social work in the justice system, 2023)
This chapter discusses the concepts of forensic social work and sociolegal social work and how in Latin America these concepts are used synonymously. The legal frameworks of Latin American and Caribbean countries are described in relation to their influence on professional social work practice. Later, the professional practices are explained in civil and criminal matters and according to how the professional role adapts to the legal framework developed in each country; meanwhile, social workers focus on users’ violation of human rights. Here, the professional practices and reflections of authors from Argentina, Brazil, Chile, Colombia, Costa Rica, Mexico, Puerto Rico, and Uruguay motivate us to reflect on and learn from their experiences of forensic social work.